2017
DOI: 10.1016/j.bbadis.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional alterations associated with deutan N94K and R330Q mutations of green cone opsin

Abstract: Deuteranopia is an X-linked congenital dichromatic condition in which single point mutations in green cone opsin lead to defective non-functional cone photoreceptor cells. Green cone opsin belongs to the G protein-coupled receptor superfamily and consists of a seven transmembrane helical apoprotein covalently bound to 11-cis-retinal, by means of a protonated Schiff base linkage, in its inactive dark state. Several point mutations in green cone opsin have been reported to cause deuteranopia, but the structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The presence of retinylidene SB in visual pigments can be measured by acidifying the sample using 2 N H 2 SO 4 to pH 1.9 (21). In the dark state, acidification disrupts the spectral tuning arising from retinal and opsin interactions, but not the protonated SB that shifts the absorbance maximum to 440 nm (21,22). Here, we used acidification to measure the regeneration of photoactivated blue cone opsin.…”
Section: Pigment Acidificationmentioning
confidence: 99%
“…The presence of retinylidene SB in visual pigments can be measured by acidifying the sample using 2 N H 2 SO 4 to pH 1.9 (21). In the dark state, acidification disrupts the spectral tuning arising from retinal and opsin interactions, but not the protonated SB that shifts the absorbance maximum to 440 nm (21,22). Here, we used acidification to measure the regeneration of photoactivated blue cone opsin.…”
Section: Pigment Acidificationmentioning
confidence: 99%
“…The reduced thermal stability of the whale shark RHO is reminiscent of cone opsins that have lower thermal stability than RHOs to enable daylight vision. In fact, compared to the human RHO (Janz et al, 2003), the whale shark RHO has lower thermal stability, which is rather closer to that of mammalian LWS/MWS (Alexander et al, 2017; Srinivasan et al, 2017) and chicken RH2 (Sato et al, 2018). Near the sea surface, the cone opsin-like low thermal stability of whale shark RHO in high-temperature water (Figure 2C) can facilitate the photoreceptor light adaptation suitable for the bright light condition.…”
Section: Discussionmentioning
confidence: 98%
“…In rhodopsin, conformational changes in Helix 8 are intimately involved in the binding process of visual arrestin, and chemical modifications of H8 inhibit arrestin binding 50 . The R330Q mutant expressed in COS‐1 cells showed decreased phototransduction activation but maintained similar thermal and chemical stabilities as normal green cone opsin 38 . The G338 residue is well conserved in vertebrate opsins.…”
Section: Discussionmentioning
confidence: 99%
“…50 The R330Q mutant expressed in COS-1 cells showed decreased phototransduction activation but maintained similar thermal and chemical stabilities as normal green cone opsin. 38 The G338 residue is well conserved in vertebrate opsins. In vitro study showed that the corresponding rhodopsin mutant G324E gave an absorbance spectrum similar to normal rhodopsin, however, G338E mutant green opsin gave no absorbance.…”
Section: Disease Mechanisms Associated With Each Of the Cone Opsin Mu...mentioning
confidence: 99%